Theory and Calculation of the Reorganization Energy of Electron Transfer at Liquid/Liquid Interface - Al-Agealy, Hadi Jabbar; Al-Saadi, Adil Ali (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A description of the theoretical of the reorganization energies have been described according to the outer-sphere Marcus model .It is a given expression according this model unable to evaluate the reorganization energy for electron transfer at liquid /liquid interface. The spherical model approach have been used to evaluate the radius of donor and acceptor liquid alternatively .Theoretical results of the reorganization free energy for electron transfer at liquid/liquid interface system was carried out . Matlap program is then used to calculate ð¸0 for electron transfer reaction between water donor stated and many liquid acceptor state. This shows a good agreement with the experiment. The results calculation shows that ð¸0 is a function of dielectric constant and refractive index and polarity of acceptor